INTEGRATION OF SOLAR PANELS AND ARDUINO FOR AQUAPONIC SYSTEM AUTOMATION AND SOLAR ENERGY EFFICIENCY - Lubis, Lailatul Husna; Mesyadi, Mesyadi; Nasution, Mulkan Iskandar (Universitas Mataram, 2025)
Aquaponics is a system that combines fish and plant farming in one mutually beneficial ecosystem. However, the consumption of electrical energy, such as driving water pumps in aquaponic systems, is crucial because it requires considerable financing. Solar panels are one of the alternatives in reducing the use of electrical energy. Solar energy is environmentally friendly and does not produce pollution like conventional energy. Thus, automation and using solar energy as renewable energy can be a solution to improving the efficiency of aquaponic systems. This research aims to analyze the Arduino-based automation system and the use of 200 Wp solar panels in aquaponics involving catfish and water spinachÂ cultivation. The system uses solar panels as the primary energy source stored in VRLA batteries, regulated through a Solar Charge Controller, and converted into AC electricity to operate the water pump and automatic monitoring system. Arduino Uno controls the automation and monitoring with pH, TDS, temperature, humidity, and ultrasonic sensors to monitor environmental conditions. Tests show that the solar panel produces an average voltage of 40.83 V and a current of 3.28 A, with an efficiency of 40.65% and a power that can be generated in a day of 1200 Watts. The operational cost of the solar panel system was calculated using the Levelized Cost of Energy (LCOE), showing that it is more efficient than PLN electricity at Rp 688.15/kWh vs. Rp 1,444.70/kWh or Rp 31,397.3 vs. Rp 65,947.35 for one year of aquaponic system use. Monitoring for 10 days showed optimal growth of water spinach and catfish plants with consistent pH, temperature, humidity, and pump and servo operation. The results indicate that an aquaponics system powered by renewable energy and Arduino-based automation effectively meets energy needs at a lower cost and improves the efficiency and reliability of aquaponics operations.